Gender research and integrated training sessions: Enhancing the quality of CGIAR gender research - CGIAR Gender and Agriculture Research Network; Pennsylvania State University (International Center for Tropical Agriculture, 2016)
The CGIAR Gender and Agriculture Research Network will be partnering with the Pennsylvania State University to develop a multi-year Gender Research and Integrated Training series for CGIAR researchers and postdoctoral fellows.